A Robust Immuno-Prognostic Model of Non-Muscle-Invasive Bladder Cancer Indicates Dynamic Interaction in Tumor Immune Microenvironment Contributes to Cancer Progression - Sun, Xiaomeng; Xu, Huilin; Liu, Gang; Chen, Jiani; Xu, Jinrong; Li, Mingming; Liu, Lei (Frontiers in Genetics, 2022)
Non-muscle-invasive bladder cancer (NMIBC) accounts for more than 70% of urothelial cancer. More than half of NMIBC patients experience recurrence, progression, or metastasis, which essentially reduces life quality and survival time. Identifying the high-risk patients prone to progression remains the primary concern of risk management of NMIBC. In this study, we included 1370 NMIBC transcripts data from nine public datasets, identified nine tumor-infiltrating marker cells highly related to the survival of NMIBC, quantified the cells’ proportion by self-defined differentially expressed signature genes, and established a robust immuno-prognostic model dividing NMIBC patients into low-risk versus high-risk progression groups. Our model implies that the loss of crosstalk between tumor cells and adjacent normal epithelium, along with enriched cell proliferation signals, may facilitate tumor progression. Thus, evaluating tumor progression should consider various components in the tumor immune microenvironment instead of the single marker in a single dimension. Moreover, we also appeal to the necessity of using appropriate meta-analysis methods to integrate the evidence from multiple sources in the feature selection step from large-scale heterogeneous omics data such as our study.